First step is to identify the slope of the line with the given equation. The general equation in point-slope form is

`y-y_0 = m(x - x_0)`

Here, `(x_0, y_0)`

is a point on the line and m is the slope. So, in the given equation, slope is m = 3.

Parallel lines have the same slope, so the line parallel to the line with the given equation has the slope m = 3 as well. Since the line in question passes through the point (0, 2), we can write its equation in point-slope form as

y - 2 = 3(x - 0)

y - 2 = 3x

y = 3x + 2

The general equation in standard form is ax + by = c, where a, b, and c are integers. To convert given equation to standard form, subtract y from both sides and subtract 2 from both sides:

0 = 3x - y + 2

-2 = 3x - y

**3x - y = -2.**

If x = -2, then y = 3(-2) + 2 = -6 + 2 = -4. **The ordered pair (-2, -4) satisfies the equation of the parallel line.**

` `